Joint costs in network services: The two-way problem in the case of unbalanced transport markets - Piet Rietveld; Roberto Roson (Fondazione Eni Enrico Mattei (FEEM), 2000)
Markets for transport are often characterised by unequal demand in both directions: every morning during peak hours the trains are crowded while moving towards the direction of large cities, whereas they may be almost empty in the other direction. In this paper we discuss the implications of these imbalances for price setting of transport firms. From the viewpoint of economic theory, two regimes can be distinguished: one where -owing to price discrimination- the flows are equal, and one where unequal flows are the result. Special attention is paid to the case where the transport firm does not apply price discrimination, as is the case in most railway firms in Europe. We find that in the case of substantial joint costs, the introduction of price discrimination not only leads to an increase of profits, but also to positive effects on consumer surplus. This result differs from the standard result in the literature on industrial economics. The standard result purports that with linear demand functions price discrimination has a negative impact on the welfare of the average consumer and that this negative impact dominates the positive effect on profits of the producer.
Keywords: 330; Öffentlicher Verkehr; Betriebliche Preispolitik; Preisdifferenzierung; Verbundvorteil; Theorie